FACIAL RECONSTRUCTION OF UNKNOWN CORPSE IN HAMA (Journal of Forensic Medicine & Toxicology, 2014)
Visual recognition may be sometimes interrupted because of decomposition and distortion of facial tissues. Facial reconstruction may be used in such cases to stimulate recognition. Using clothes of the corpse in this procedure may be helpful.
Keywords: cadaver; thirteen’s